Evaluation of intraoperative cytological assessment of bone resection margins in patients with oral squamous cell carcinoma. Issue 9 (18th April 2014) - Nieberler, Markus; Häusler, Patrick; Drecoll, Enken; Stoeckelhuber, Mechthild; Deppe, Herbert; Hölzle, Frank; Kolk, Andreas; Wolff, Klaus‐Dietrich; Kesting, Marco Rainer; Weirich, Gregor
<x xml:space="preserve">Abstract</x> BACKGROUND Frozen sections are routinely applied to control for adequate resection margins. In cases in which carcinoma infiltrates bone, the intraoperative microscopic assessment of bone margins remains challenging due to technical difficulties to section native bone. The objective of the current study was to evaluate an intraoperative cytological approach to control bone resection margins in patients with bone‐infiltrating oral squamous cell carcinomas. METHODS A total of 174 cytological preparations obtained from bone margins of bone‐infiltrating oral squamous cell carcinomas (28 patients) were assessed intraoperatively and compared with the corresponding histological findings. In a validation cohort (45 patients) the intraoperative cytological assessment of bone resection margins (ICAB) (104 margins) was evaluated as a diagnostic tool for routine clinical application. RESULTS In the first patient cohort, the ICAB revealed 95.3% sensitivity and 96% specificity. The results provided an accuracy of 95.7% with a significant correlation noted between cytological and histological results (κ, 0.91; P < .001), and a positive predictive value and negative predictive value of 93.8% and 96.9%, respectively. In the validation cohort, ICAB revealed 80% sensitivity and 98.9% specificity with 98% accuracy. There was a significant correlation found between cytological and histological results (κ, 0.91; P < .001), providing a positive predictive value and negative predictive value of 80% and 98%, respectively. ICAB could predict final resection status at bone margins with 80% sensitivity and 97.5% specificity. A significant correlation was found between the cytological and histological resection status at bone margins (κ, 0, 75; P < .001). CONCLUSIONS ICAB could supplement intraoperative frozen sections of soft tissue margins as a standard procedure to control for adequate resection at bone margins. Cancer (Cancer Cytopathol) 2014;122:646–656. © 2014 American Cancer Society.